ANALISIS DAN PENGEMBANGAN INOVASI PEMBELAJARAN PPKN DI SMP, SMA DAN PERGURUAN TINGGI - Suwardi Suwardi (Ensiklopedia Education Review, 2022)
The reasoning and problem solving model in learning has five learning steps, namely: (1) reading and thinking (identifying facts and problems, visualizing situations, describing solution settings, (2) exploring and planning (organizing information, drawing solution diagrams, making tables, graphs, or figures), (3) selecting strategies (setting patterns, testing patterns, simulations or experiments, reduction or expansion, logical deduction, writing equations), (4) finding answers (estimating, using computational, algebraic, and geometry), (5) reflection and expansion (correcting answers, finding other alternative solutions, expanding concepts and generalizations, discussing solutions, formulating original varied problems) The developing social system is the lack of the teacher's role as a transmitter of knowledge, democratic, teacher and students have the same status, namely facing problems, interactions are based on problems deal. The reaction principle developed is that the teacher acts more as a counselor, consultant, source of constructive criticism, facilitator, high-level thinker. This role is shown mainly in the process of students carrying out problem solving activities. The learning tools needed are in the form of confrontational material that is able to generate basic, critical, creative thinking processes, higher-order thinking, and non-routine problem solving strategies, and non-routine problems that challenge students to make reasoning and problem solving efforts. As the impact of learning in this model is understanding, critical and creative thinking skills, problem solving skills, communication skills, skills to use knowledge meaningfully. While the accompanying impact is the tentative nature of the scientist, scientific process skills, autonomy and freedom of students and students, tolerance for uncertainty and non-routine problems.Keywords: Innovation, Learning, Civics, Junior High School, Senior High School, Higher Education.